Teatro empresarial: a trajetória empreendedora da Itaguari cultural - TEIXEIRA, Silvia Dutra (2022)
This Course Conclusion Work shows the Itaguari Culture Corporate Theater down the business way, artistic promoter localized on 204 Santa Catarina Lane apt. 402.This searching has like objective to comprehend what means the corporate theater and how this methodological process goes on acting camp based n Itaguari experience way. Emphasizing yet the scenic language importance in corporative sphere and like creative economy’s sector. This moment entrepreneurs’ searching, starting this comprehension to conceptualize the corporate theater.